Phalangeal autologous bone graft for flail digit subluxation: A case report. (June 2022) - Uddin, Akram; Bramall, John; Santos, Derek
A 70-year-old patient was referred for a surgical opinion with a flail digit. Flail digit occurs as a result of over resection to the head of the proximal phalanx beyond the surgical neck and proximally into the shaft. The patient was complaining of a symptomatic right fourth digit (pain 7/10 on a Visual Analogue Scale) that had previously undergone two failed hammer toe surgeries resulting in symptomatic plantar hyperkeratosis with no history of ulceration or infection. The patient was surgically managed with autologous bone graft harvested from an adjacent digit biphalangic phalanx. Six months postoperative, the patient presented asymptomatic. Anatomical alignment, digital stabilisation and function were achieved. Full autologous graft consolidation was confirmed radiographically. Favourable patient-reported outcomes using the Manchester–Oxford Foot Questionnaire showed improvement in all domains. Currently, there is no published case study or description utilising our surgical technique to treat flail digit deformity.